Pesantren dan Islam Wasathiyah: Ulama, Tradisi intelektual dan Akar Sosial Moderasi Islam - Fadlan, Muhammad Nida'; Munhanif, Ali; Azmi, Agus Nilmada (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
Pesantren as Islamic educational institutions have undergone institutional transformation. Pesantren have been able to become a means for the emergence of a new generation of Muslim educated people who are familiar with modern terms. This research will examine how socio-political attitudes and orientations develop in pesantren today. The pesantren that become the object of this research are Pesantren Buntet Cirebon, Pesantren Tebuireng Jombang, and Pesantren API Tegalrejo. Through these pesantrens, this research will look at the extent to which thecontinuity aspect of the pesantrens in maintaining their traditions over the centuries.  In addition, this study will also capture thechanges experienced by pesantren in responding to the development of attitudes and behaviors regarding contemporary and religious issues. Through the two aspects above, this research is expected to obtain an overview of the views of kyai and pesantren in viewing the idea of Wasathiyah Islam, especially related to issues of socio-cultural plurality, tolerance, democracy, and issues of civic values that develop in society.